PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KETERLIBATAN KARYAWAN DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL INTERVENING (STUDI PADA MG SETOS HOTEL SEMARANG) - Ardianto, Prama Suryo; Yuniawan, Ahyar (Diponegoro Journal of Management, 2020)
The hotel business is a service that requires entrepreneurs to always provide the best service and performance at all times, twenty-four hours a day. When talking about service, it cannot be separated from what is called human resources. The most common problems in the hotel business are the level of performance and service that is not always optimal, and the high risk of turn over for employees. Employee engagement is one way to overcome these problems. Many factors can affect the level of employee engagement, including transformational leadership, applied organizational culture, and the level of emotional intelligence each employee has.The data analysis method used in this study is Structural Equation Modeling, which is estimated by the AMOS program. The study was conducted on employees of the MG SETOS Hotel Semarang. This study involved 127 respondents who were randomly selected through simple random sampling technique.This study examines the effect of transformational leadership and organizational culture on the level of employee engagement with emotional intelligence being its intervening variables. The results of this research indicate a positive influence between transformational leadership and organizational culture on emotional intelligence, the positive influence of transformational leadership and organizational culture on employee engagement,Â  and a positive influence between emotional intelligence on employee engagement. In conclusion, this research is able to prove the proposed hypothesis.